L’influence de la volition sur la distribution des verbes à alternance causative dans les résultatives de l’anglais - Maryse Grône (Anglophonia)
This article is a detailed examination of the distribution of verbs undergoing the causative/inchoative alternation in the English resultative. More precisely, the purpose of this paper is to show, on the basis of an extensive corpus investigation of naturally occurring data, that already-existing analyses of the resultative structure – Simpson 1983, Levin & Rappaport Hovav (L&RH) 1998, 1999, 2001, Wechsler 1997 – are insufficient to account for the full range of data collected. On the one hand, Simpson’s and L&RH’s approaches fail to make accurate predictions as to the distribution of alternating change of state verbs in the resultative frame. On the other hand, although Wechsler’s analysis is much more promising, I show that it nonetheless needs to be refined in light of a previously unnoticed fact. Indeed, the distribution of verbs undergoing the causative/inchoative alternation in the COCA indicates that their intransitive variants are much more likely to occur in resultatives than their transitive counterparts. In order to account for this phenomenon, I propose that a new explanatory factor, namely volitionality, influences the acceptability of alternating verbs in the resultative frame.